2016
DOI: 10.1038/srep29504
|View full text |Cite
|
Sign up to set email alerts
|

Deciduous trees are a large and overlooked sink for snowmelt water in the boreal forest

Abstract: The terrestrial water cycle contains large uncertainties that impact our understanding of water budgets and climate dynamics. Water storage is a key uncertainty in the boreal water budget, with tree water storage often ignored. The goal of this study is to quantify tree water content during the snowmelt and growing season periods for Alaskan and western Canadian boreal forests. Deciduous trees reached saturation between snowmelt and leaf-out, taking up 21–25% of the available snowmelt water, while coniferous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 31 publications
4
37
0
Order By: Relevance
“…In contrast, Kevo showed a substantial water surplus (Table ). Our measurements did not include the snowmelt period, but these sites can reach snowpack depths of >1 m (data not shown), and tree water uptake during this period, especially from deciduous species, can progressively deplete soil water sources (Young‐Robertson et al, ). This decline in soil water content after snowmelt is very clear in the seasonal course of SMD measured in Abisko in 2008 and 2009 (outside our measurement period in Abisko, Figure S5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Kevo showed a substantial water surplus (Table ). Our measurements did not include the snowmelt period, but these sites can reach snowpack depths of >1 m (data not shown), and tree water uptake during this period, especially from deciduous species, can progressively deplete soil water sources (Young‐Robertson et al, ). This decline in soil water content after snowmelt is very clear in the seasonal course of SMD measured in Abisko in 2008 and 2009 (outside our measurement period in Abisko, Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…Higher transpiration rates by deciduous broadleaf forests could lead to stronger evaporative cooling locally (Chapin et al, ), although, in a regional context, the effects of the expansion of deciduous broadleaf trees into the tundra zone can be more complex and actually enhance Arctic warming (Swann et al, ). Moreover, increased soil moisture uptake by deciduous trees could lead to faster depletion of snowmelt water during the shoulder season, triggering further hydrological changes (Young‐Robertson, Bolton, Bhatt, Cristóbal, & Thoman, ). Therefore, a greater understanding of the magnitudes and controls of evapotranspiration in deciduous woodlands is needed to predict future changes in land–atmosphere interactions in subarctic forest–tundra ecotones.…”
Section: Introductionmentioning
confidence: 99%
“…For example, temperature sensitivity of spring tree growth, water use, and successional strategy vary dramatically between the dominant angiosperm and gymnosperm species (Drobyshev, Gewehr, Berninger, Bergeron, & Mcglone, ; Euskirchen, Carman, & Mcguire, ; Hollingsworth, Johnstone, Bernhardt, & Chapin, ; Johnstone & Chapin, ; Trugman et al., ; Young‐Robertson, Bolton, Bhatt, Cristobal, & Thoman, ). Site‐level studies have shown that angiosperm water use greatly exceeds that of gymnosperm species in the Alaskan boreal forest, such that angiosperm species consume >20% of total snowmelt water in comparison to the <1% associated with gymnosperm species (Young‐Robertson et al., ). Understanding angiosperm vs. gymnosperm responses to climate change is particularly important given that recent fires in Alaska have the potential to increase angiosperm coverage by up to 20% (Barrett, Mcguire, Hoy, & Kasischke, ).…”
Section: Introductionmentioning
confidence: 99%
“…3c, Table 3). The permafrost coverage is different between the two sub-basins, with approximately 2 and 53 % in the LowP and HighP sub-basins, respectively (Table 1; Rieger et al, 1972;Yoshikawa et al, 2002).…”
Section: Study Areamentioning
confidence: 99%
“…Location and permafrost extent (light blue shading) in the Caribou Poker Creek Research Watershed, Alaska, and the two subbasins of interest (low permafrost or LowP sub-basin and high permafrost or HighP sub-basin). The permafrost map of CPCRW was produced by a small-scale observation across the watershed (Rieger et al, 1972;Yoshikawa et al, 2002). hydrological model. The sub-grid parameterization method proposed in this study closely fits the MPR approach.…”
mentioning
confidence: 99%